Avaliação de indicadores de impactos ambientais no perímetro irrigado Cruzeta-Região semi-árida do RN - Oliveira, Luciana Caldeira de (2009)
Environmental impacts are defined as the processes of social and ecological changes caused by nuisance ambient. In agriculture are diverse, and the intensive use of land and inappropriate agricultural practices causes negative effect on the environment besides affecting crop productivity and quality of life of man. So this study was objective to analyze parameters indicators of environmental impacts in the Cruzeta the Discrict Irrigation. During the period July 2007 to March 2008 samples were collected in lot 01 and 02 of the irrigation district. The monitoring was conducted in four sampling points, three (3) located in the irrigation channels and 1 (one) located in a cacimbão. Were monitored pH, CE, STD, SS, NO3-, OD, DT, PST, RAS, CT, Ca+2, Mg+2, Na+ and K+ and heavy metals. Analysis was performed, soil fertility, determining the infiltration rate, moisture content of soil and flow measurement. The results showed that the parameters considered most effective in evaluating the indicators of environmental impacts were: Suspended solid, turbidity, dissolved oxygen and Coliform termotelerantes. The concentrations of nitrate were below the limit established by CONAMA (2005). High levels of STD were found in the point P4. The risk of salinity in cacimbão Lot 02, the water was classified as Class II, or medium risk of salinity in the remaining points was classified as Class I. The iron and aluminum were found high concentrations in four sampling points independent of the dry or rainy. On the ground, found high levels of phosphorus in both samples collected in the batch 01, as the lot 02. The pH levels found in samples of soil, the soil can be classified as neutral and moderate alkalinity. The high infiltration rate obtained in the tests performed in lots 01 and 02 indicated the high permeability of soil at these points